[PP.19.22] VALIDATION OF A NEW CENTRAL AORTIC PRESSURE MEASUREMENT EQUIPMENT AORTIC COMPARED WITH SPHYGMOCOR. (September 2017) - Cuffaro, P.; Morales, M.; Rada, M.; Galarza, C.; Alfie, J.; Marin, M.; Micali, R.; Barochiner, J.; Aparicio, L.; Waisman, G.
Abstract : Objective: To validate a new non-invasive Central Aortic Pressure (PAC) equipment by Aortic radial tonometry compared to Sphygmocor. Design and method: Subjects from 18 to 80 year old, stratified into 3 groups: <30, 30–60 > 60 years with equal number of hypertensive and healthy volunteers in each stratum. Exclusion criteria: BMI>30 Kg/m 2, pregnancy, arrhythmias, wrist surgery or alterations that prevented radial pulse measurement. Anthropometric measurements were performed, the brachial blood pressure (BP) was measured in triplicate, so standardized with automatic device (OMROM HEM 705CP). Three measurements of the PAC were performed with the Aortic equipment (PACAort) and 3 with the Sphygmocor (PACSphyg) alternately, on the right side, without previous consumption of alcohol and coffee. Statistical analysis: Bland-Altman method to evaluate the degree of agreement between the measurements of both devices. The recommendations of the American Association for the Advancement of Medical Instruments (AAMI) were considered for the assessment of the degree of agreement: mean differences <5 mmHg and standard deviation <8 mmHg. Protocol approved by the institutional ethics committee. The study was carried out independently and for academic purposes. Results: 85 subjects, mean age 46 (18–80); 45 women and 40 men; BMI 25.1 ± 2.8; 6 measurements performed per patient (total 510 determinations). The PACAort was strongly correlated with the PACSphyg (R 2 0.96; y = 0.31 + 0.99 p < 0.001). The mean PACSphyg was 109.3 ± 12.05 mmHg, the average PACAort 109.0 ± 12.2 mmHg. No bias or proportionality observed. The Bland-Altman method showed: mean of differences (PACSphyg - PACAort) 0.35 ± 2.43 mmHg (95% CI - 0.17 to 0.87). The coefficient of repeatability was 9.48 and coefficient of variation was 4.8% for Sphygmocor and 9.91 and 4.9% for Aortic. Figure. No caption available. Conclusions: Measurement of PAC with Aortic equipment shows an excellent degree of agreement with Sphygmocor.